PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV B SDN 21 SITORAJO KECAMATAN KUANTAN TENGAH - Arlinda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low learning outcomes of students' IPS, from 22 students only 10 (45.45%) reaching the determined KKM, in addition the average student learning outcome is 62.50. The study aims to improve the learning outcomes of IPS Through the application of TSTS learning model. This research is a classroom action research, this research is conducted in SDN 21 Sitorajo Kecamatan Kuantan Tengah. Subjects in this study were students of class IV B with a total of 22 students. This research is conducted two cycles with four stages, namely: planning, implementation, observation and reflection. The result of research stated that after applied cooperative learning model type TSTS can improve learning result of IPS. This is evidenced by: (a) teacher activity in cycle I is 62,50, in cycle II equal to 82,81. Student activity in cycle I earn 65,62, in cycle II equal to 85,93; (b) result of student learning on prasiklus equal to 62,50, at cycle I equal to 72,50 and at second cycle equal to 82,18.